Comparison between powerful Waterpik flosser with dental floss as an adjunct to tooth brushing - Hadeel M Akram (College of Dentistry/ University of Baghdad, 2015)
Background: Removing dental plaque is important to maintain a good oral hygiene and prevent periodontal disease; this could not be accomplished by the use of toothbrush alone, it needs the help of interdental aids or intra-oral irrigator devices. The aim of this study was to compare the effect of using Waterpik flosser as adjunct to tooth brushing than using the dental floss with the brushing. Materials and methods: A single blind, six weeks study included 45 subjects divided into three groups of 15 subjects at each group. Group B (brushing) was instructed to use the toothbrush only, group BF (brushing & flossing) was instructed to use dental floss and tooth brushing while group BW (brushing and Waterpik flosser) was instructed to use Waterpik flosser in addition to the toothbrush. Plaque index, gingival index and bleeding on probing were measured at the 1st visit, after 3 weeks (2nd visit) and finally after 6 weeks (3rd visit). Results: The plaque index was significantly reduced in group BF and BW at the 3rd visit, while it showed no significant differences in group B. The mean percentage reduction of gingival index at the 3rd visit was higher in group BW than group B and group BF. Using the chi-square test, bleeding on probing showed no significant difference in group B, while there was significant reduction in group BF and highly significant reduction (p